The Role of p24 Immunohistochemistry to Identify HIV Lymphadenitis - Muhartono Muhartono; Indri Windarti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2020)
Introduction : That was a difficulty to diagnose the early stage of HIV while the symptoms was only enlargement of the lymph nodes, so that the pattern A of HIV lymphadenitis that presented on histopathological examination is expected to be a determinant of early-stage. Although the staining of p24 antibody has already be used to detect HIV infection in the tissue, but the positivity of p24 in pattern A HIV lymphadenitis has not been investigated. Aim of study : To identify pattern A of HIV lymphadenitis on histopathological examination and to identify p24 antibody to be a determinant of early-stage HIV infection. Methods : This is a retrospective descriptive study. We collected 64 cases of non spesific lymphadenitis from the Anatomical Pathology archive, Cipto Mangunkusumo hospital and examined these cases by using the criteria of pattern A HIV lymphadenitis in the tissue specimen. Then we performed the staining of p24 antibody by immunohistochemistry. Results : There were twelve by sixty four (12/64) cases of that have pattern A HIV lymphadenitis on microscopic evaluation. Only three cases was clinically noted as Acquired Immunodeficiency Syndrome (AIDS) by clinician, while 11 of 12 cases showed immunohistochemistry positive for p24 antibody. Conclusion : Most of the patten A HIV lymphadenitis (11/12) showed the positive staining for p24 antibody. In patients who had received Anti Retro Viral (ARV) therapy, the staining of p24 antibody was negative. This study still needs more samples, the serologic data of the patient to be more reliable.